2017
DOI: 10.20452/pamw.4140
|View full text |Cite
|
Sign up to set email alerts
|

Leukotrienes biosynthesis in coronary artery disease - results of Leukotrienes and Thromboxane In Myocardial Infarction (LTIMI) study

Abstract: INTRODUCTION Leukotrienes (LTs) may be involved in atherosclerosis and may contribute to cardiovascular outcomes in CAD. OBJECTIVES    We aimed to compare the baseline LT production in patients with stable CAD (sCAD) and myocardial infarction (MI), and to assess whether an increased LT production is associated with major adverse cardiovascular events (MACEs) at 1 year after MI. PATIENTS AND METHODS    LTIMI (Leukotrienes and Thromboxane In Myocardial Infarction) was a single‑center, prospective, observational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…This effect of MK can be attributed to its anti-inflammatory and antioxidant effects [88]. A single-center, prospective, observational study showed that patients with previous myocardial infarction had higher urinary LTs as compared with unstable angina [89].…”
Section: Montelukast and Myocardial Infarctionmentioning
confidence: 99%
“…This effect of MK can be attributed to its anti-inflammatory and antioxidant effects [88]. A single-center, prospective, observational study showed that patients with previous myocardial infarction had higher urinary LTs as compared with unstable angina [89].…”
Section: Montelukast and Myocardial Infarctionmentioning
confidence: 99%